2016
DOI: 10.1111/acer.13245
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Behavioral Economic Predictors of Stable Moderation Drinking Among Problem Drinkers Attempting Natural Recovery

Abstract: Background As interventions have expanded beyond clinical treatment to include brief interventions for persons with less severe alcohol problems, predicting who can achieve stable moderation drinking has gained importance. Recent behavioral economic (BE) research on natural recovery has shown that active problem drinkers who allocate their monetary expenditures on alcohol and saving for the future over longer time horizons tend to have better subsequent recovery outcomes, including maintenance of stable modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
5
24
2
Order By: Relevance
“…These relationships have not been well investigated among persons with AUD who attempted natural recovery, even though moderation is a relatively more common outcome in untreated samples, in part because treatment-seeking is associated with higher problem severity (Fan et al, 2019;Tucker et al, 2004), and most treatment programs emphasize abstinence. Therefore, in 5 prospective studies of natural recovery attempts guided by behavioral economics (Tucker et al, 2016(Tucker et al, , 2008(Tucker et al, , 2012(Tucker et al, , 2006(Tucker et al, , 2002, we investigated moderation predictors and replicated the support found in treatment studies for lower alcohol dependence and alcohol-related problems. We also developed and assessed a novel temporally sensitive behavioral economic measure of the reward value of drinking in relation to nondrinking commodities, the "Alcohol-Savings Discretionary Expenditure" (ASDE) index.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…These relationships have not been well investigated among persons with AUD who attempted natural recovery, even though moderation is a relatively more common outcome in untreated samples, in part because treatment-seeking is associated with higher problem severity (Fan et al, 2019;Tucker et al, 2004), and most treatment programs emphasize abstinence. Therefore, in 5 prospective studies of natural recovery attempts guided by behavioral economics (Tucker et al, 2016(Tucker et al, , 2008(Tucker et al, , 2012(Tucker et al, , 2006(Tucker et al, , 2002, we investigated moderation predictors and replicated the support found in treatment studies for lower alcohol dependence and alcohol-related problems. We also developed and assessed a novel temporally sensitive behavioral economic measure of the reward value of drinking in relation to nondrinking commodities, the "Alcohol-Savings Discretionary Expenditure" (ASDE) index.…”
mentioning
confidence: 74%
“…An expanded Timeline Followback (TLFB) interview (Sobell and Sobell, 1992;Vuchinich et al, 1988) conducted at both data collection points assessed drinking practices, income, and expenditures covering the preceding year, which generated detailed behavioral records covering the 2 years surrounding sobriety onset. Select studies also included interactive voice response data collection (Tucker et al, 2016(Tucker et al, , 2008(Tucker et al, , 2012 and had longer (Tucker et al, 2002(Tucker et al, , 2006 or more frequent (e.g., quarterly) follow-ups (2008,2012,2016). Measures are described next and in earlier publications.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, laboratory studies suggested that impulsivity, when assessed in several different ways, does not directly predispose individuals to problem drinking (Mullen et al, 2016, Stevens et al, 2017). In community dwelling problem drinkers, a money-based “Alcohol-Savings Discretionary Expenditure” index but not analogous measures of behavioral impulsivity predicted stable moderation drinking (i.e., longer-term behavior regulation) compared to stable abstinence or relapse (Tucker et al, 2016). …”
Section: Introductionmentioning
confidence: 95%